Dialogbook: a proposal for simple e-portfolio system for international communication learning. Issue 5 (23rd October 2020) - Iio, Jun; Wakabayashi, Shigenori
Abstract : Purpose: Many learning management systems and e-portfolio services that are useful for recording learners' activities and facilitating communication among students and teachers have been proposed. However, current implementations have several problems. One major issue is that the users of the services provided by these applications are restricted to licensed users only. Another problem is that it is usually impossible for third parties to retrieve the recorded data for research purposes. Therefore, the purpose of this paper is to implement a simple e-portfolio system to keep records of outputs from the students for the classes. Design/methodology/approach: The authors developed a system called Dialogbook to help students participating in international communication courses, which provides a simple e-portfolio service and can be used from plural schools. Findings: Before using the system in this plan of the international communication courses, the authors checked its values by using it in a mathematics course, which was provided in the university by one of the authors. This paper describes brief reports of the efficiency of the system. This system disclosed the tendencies of self-scoring by participants in the courses. Originality/value: This paper describes the efficiency of the proposed system for international communication courses that will be held between two or more than two schools. It can be easily used with an interorganizational education project.